Adsorption of Cd2+ and Cr3+ ions from aqueous solutions by using residue of Padina gymnospora waste as promising low-cost adsorbent. Issue 3 (March 2019) - Mohamed, Hussein S.; Soliman, N.K.; Abdelrheem, Doaa A.; Ramadan, Arwa A.; Elghandour, Ahmed H.; Ahmed, Sayed A.
Abstract: Recently, a great attention has been given for applying a low-cost and effective adsorbents instead of expensive and dangerous chemical materials as a promising approach to treat wastewater. In this work, residue powder of brown macroalga Padina gymnospora (RPG), after extracting most of its active components by 70% methanol, was used as an adsorbent material for wastewater treatment. This work also reduces the costs of residue disposal. The adsorption ability of RPG is studied for removing Cd 2+ and Cr 3+ from wastewater. We investigated metal adsorption isotherms and kinetics, the effect of initial metal concentration, contact time, adsorbent dosage, temperature, pH and the RPG reusability on metal ions removal. The results showed that the removal % generally increases with decreasing concentration of metal ions. RPG has higher metal removal percentages reaching 96.2% and 78.8% for Cd 2+ and Cr 3+, respectively, with a maxiumum adsorption capacity of 96.46 and 31.52 mg/g forCd 2+ and Cr 3+, respectively at pH 6.2, 50 mg, 25 °C and initial metal concentration of 100 mg/L. The metal ions removal % increased by increasing the dosage of adsorbent and it decreased after a certain limit. The metal removal % slightly changes with increasing temperature for Cd 2+ and decreased at high-temperature for Cr 3+ . The adsorption increased with increasing pH value from 3 to 5, and decreases at pH value of 6.2 then it increased again at pH 8. The removal % and adsorption capacity at pH 8 reaches 99.58%, 99.65%, 99.85 mg/g and 39.86 mg/g for Cd 2+ and Cr 3+, respectively. The results also showed that RPG can be reused several times for metal ions removal. In addition, Tempkin isotherms and pseudo-second-order kinetic fit the adsorption of Cd 2+ and Cr 3+ well.